Nano-composite system and intelligent controlled-release microneedle patch for treating leucoderma and preparation method of nano-composite system and intelligent controlled-release microneedle patch
The intelligent controlled-release system using enzyme-responsive micelles and polydopamine nanoparticles solves the problems of uneven drug delivery and multiple pathological interventions in the treatment of vitiligo, achieving efficient drug delivery and controlled release at the lesion site, and significantly improving vitiligo symptoms.
Patent Information
- Application Number
- CN202511714411.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2025-12-19
- Estimated Expiration
- 2045-11-21
AI Technical Summary
Existing methods for treating vitiligo are difficult to simultaneously address oxidative stress, inflammatory responses, and pigment regeneration disorders, and also suffer from problems such as uneven drug delivery, complex material preparation, and poor skin adhesion.
A smart controlled-release system using enzyme-responsive micelles and polydopamine nanoparticles was employed, and a nanocomposite system was constructed using soluble microneedle technology to achieve multiple synergistic interventions on the pathological microenvironment of vitiligo, including the regulation of oxidative stress, inflammatory response, and pigment regeneration disorders.
It achieves efficient delivery and controlled release of drugs at the lesion site, significantly improves vitiligo symptoms, promotes skin repigmentation, and has good biocompatibility and is suitable for large-scale production.
Smart Images

Figure CN121154520A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of biological medicine and dermatosis treatment, and particularly relates to a nano-composite system for treating vitiligo and an intelligent controlled-release microneedle patch. BACKGROUND
[0002] Vitiligo is a chronic depigmenting disease characterized by progressive loss of skin melanocytes, with a global prevalence of about 1%-2%. This disease not only brings heavy psychological burden to patients, but also significantly increases the risk of skin cancer due to the decline of epidermal photoprotection. Current research suggests that the pathogenesis of vitiligo revolves around the pathological cycle of "oxidative stress-immune inflammation-melanocyte dysfunction". Among them, oxidative stress is the core starting link, and the patient's melanocytes have inherent defects, leading to excessive accumulation of reactive oxygen species (ROS), while key antioxidant enzymes such as catalase (CAT) and superoxide dismutase (SOD) are damaged, causing imbalance of the oxidation-antioxidant system. Persistent oxidative stress further triggers an immune inflammatory cascade through mechanisms such as promoting T lymphocyte activation and enhancing melanocyte immunogenicity, ultimately forming a step-by-step amplification of the melanocyte destruction cycle.
[0003] Current clinical mainstream treatment methods include topical calcineurin inhibitors, narrow-band ultraviolet B (NB-UVB) phototherapy, and surgical transplantation, etc. However, these methods have obvious limitations in achieving stable repigmentation: topical drugs have limited efficacy outside the face and neck, and may cause skin irritation; phototherapy has a long treatment period, low complete repigmentation rate, and high recurrence rate after drug withdrawal; surgical transplantation is limited by the Koebner phenomenon and the risk of trauma. These current situations highlight the difficulty of existing technology in simultaneously intervening in multiple interconnected aspects of the pathological process of vitiligo.
[0004] In recent years, plant-derived nanovesicles (pNVs) have become a promising drug delivery platform due to their inherent biocompatibility and biodegradability. In particular, ginseng-derived exosomes (G-Exos) have become an ideal candidate for restoring melanocyte function and immune homeostasis due to their excellent antioxidant and anti-inflammatory efficacy. At the same time, polydopamine nanoparticles (PDA) as a biomimetic substitute for melanin not only provide immediate optical compensation through pigment deposition, but also effectively scavenge ROS through their phenolic hydroxyl groups, synergistically enhancing antioxidant defenses.
[0005] However, the single preparation form has obvious defects: the exosomes are directly applied and are easily hindered by the skin barrier, and it is difficult to effectively enrich at the lesion site; lack of lesion targeting and controlled release ability, easy to cause drug waste; unable to realize the synergistic intervention of oxidative stress, inflammatory damage and pigment regeneration in space and time. The existing drug delivery systems such as CN202110203774.4, CN201810643146.6 and the like disclosed exosome controlled release hydrogel still face problems such as complex material preparation, difficult to administer by minimally invasive method, poor adhesion at the action site and the like.
[0006] Therefore, there is an urgent need in the art to develop a new delivery system that can penetrate the skin barrier, realize lesion targeting, and respond to pathological microenvironment for intelligent drug release, to simultaneously regulate multiple key links of vitiligo pathogenesis, and break through the limitations of existing treatment technologies. SUMMARY
[0007] Based on the above reasons, the present application provides a nano-composite system and an intelligent controlled-release microneedle patch for treating vitiligo. Specifically, the present application aims to construct an intelligent responsive drug delivery system by using soluble microneedle technology to encapsulate ginseng root-derived exosomes (G-Exos) and polydopamine-polyethylene glycol nanoparticles (PDA@PEG), so as to realize the multiple synergistic intervention of oxidative stress, inflammatory response and pigment regeneration disorder in the pathological microenvironment of vitiligo. The present application can meet the treatment scenarios of vitiligo lesions at different sites and stages. The purpose of the present application can be achieved by the following technical solutions: The present application first provides a nano-composite system for treating vitiligo, characterized in that it contains enzyme-responsive micelles and polyethylene glycol-modified polydopamine nanoparticles; the enzyme-responsive micelles are formed by encapsulating ginseng root-derived exosomes with glyceryl monostearate (TM); and the polyethylene glycol-modified polydopamine nanoparticles are composed of a polydopamine core and methoxy-polyethylene glycol-amine through covalent connection.
[0008] In one embodiment of the present application, the average hydrodynamic diameter of the polyethylene glycol-modified polydopamine nanoparticles is 150-170 nm, and the Zeta potential is -15 mV to -25 mV.
[0009] In a preferred embodiment of the present application, the polyethylene glycol-modified polydopamine nanoparticles are prepared by covalent connection of dopamine basic oxidative polymerization and PEG-NH2.
[0010] The present application further provides a preparation method of the above-mentioned nano-composite system, characterized by comprising the following steps: (a) Extraction of ginseng root-derived exosomes: ginseng root-derived exosomes are extracted and purified from ginseng root tissues by differential centrifugation and sucrose density gradient centrifugation; (b) Preparation of enzyme-responsive micelles: a glyceryl monostearate aqueous solution is mixed with a ginseng root-derived exosome solution, ultrasonic emulsification and dialysis purification are performed, and the enzyme-responsive micelles are obtained; (c) Preparation of polyethylene glycol-modified polydopamine nanoparticles: dopamine is polymerized under alkaline conditions to form polydopamine nanoparticles, and after purification, the polydopamine nanoparticles are mixed with a methoxy-polyethylene glycol-amine solution, ultrasonic-assisted reaction and dialysis purification are performed, and the polyethylene glycol-modified polydopamine nanoparticles are obtained.
[0011] Another aspect of the present application provides an intelligent controlled-release microneedle patch for treating vitiligo, characterized in that the needle tip matrix of the patch is loaded with the above-mentioned nanocomposite system.
[0012] In a preferred embodiment of the present application, the needle tip matrix material of the microneedle is made of a polymer. Suitable polymers include, but are not limited to, hyaluronic acid, polyvinyl alcohol, alginate, gelatin, chitosan and derivatives thereof, which are used alone or in combination in the present application, and methacrylated hyaluronic acid (HAMA) and polyvinyl alcohol (PVA) are more preferred.
[0013] Each microneedle is arranged on a base layer to form a microneedle patch. The base layer is also composed of a polymer, including but not limited to polyvinyl alcohol, sodium carboxymethyl cellulose, alginate and polyvinylpyrrolidone, etc., which are used alone or in combination in the present application, and polyvinyl alcohol is more preferred.
[0014] In an embodiment of the present application, the mass concentration of methacrylated hyaluronic acid in the needle tip matrix is 3% to 8%, and the mass concentration of polyvinyl alcohol is 0.5% to 2%.
[0015] In the microneedle patch of the present application, a plurality of microneedles are arranged in a regular pattern. According to some embodiments, the distance between each microneedle is equal. The microneedle shape includes but is not limited to conical and prismatic, and conical is more preferred. The needle height is 700-800 μm, and the needle base diameter is 450-550 μm.
[0016] In an embodiment of the present application, 80-120 microneedles are arranged on a base layer with an area of 1 cm 2 .
[0017] Another aspect of the present application provides a preparation method of the above-mentioned intelligent microneedle patch, characterized in that it comprises the following steps: (a) Dissolve methacrylated hyaluronic acid, polyvinyl alcohol and a photoinitiator in water to form a base solution; (b) Mix the above-mentioned nanocomposite system with the base solution to obtain a needle tip matrix solution; (c) injecting the needle tip matrix solution into a microneedle mold, after centrifugal filling, pre-drying, UV cross-linking curing, and covering with a backing layer, the microneedle patch is obtained after demolding.
[0018] Another aspect of the present application provides a pharmaceutical composition, characterized in that it comprises a therapeutically effective amount of the above-mentioned nanocomposite system and a pharmaceutically acceptable carrier.
[0019] Another aspect of the present application provides a kit containing the above-mentioned intelligent microneedle patch, which consists of a microneedle patch and physiological saline packaged separately.
[0020] Another aspect of the present application provides the use of the above-mentioned nanocomposite system or the above-mentioned intelligent microneedle patch in the preparation of a medicament for preventing and / or treating vitiligo.
[0021] Another aspect of the present application provides the use of the above-mentioned nanocomposite system or the above-mentioned intelligent microneedle patch in the preparation of a medical device or a cosmetic product for antioxidant and / or anti-inflammatory purposes.
[0022] Compared with the prior art, the present application has the following beneficial effects: The nanocomposite system of the present application realizes multiple intervention on oxidative stress, inflammatory response and pigment regeneration disorder in the pathological microenvironment of vitiligo through the synergistic effect of enzyme-responsive micelles and polydopamine nanoparticles. The microneedle patch of the present application can effectively penetrate the stratum corneum of the skin to achieve efficient drug delivery, and at the same time, through the intelligent response characteristics, it can achieve controllable release of the drug at the lesion site. The preparation method provided by the present application is simple in process and mild in conditions, and is suitable for large-scale production. Animal experiments have confirmed that the microneedle patch provided by the present application can significantly improve the skin lesion symptoms of the vitiligo model, promote the repigmentation of hair and skin, and has good biological safety. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 Reaction mechanism diagram of PDA@PEG synthesis process.
[0024] Figure 2 Schematic diagram of microneedle patch production and release mechanism.
[0025] Figure 3 TEM image of G-Exos.
[0026] Figure 4 Hydrodynamic particle size and Zeta potential distribution diagram of G-Exos.
[0027] Figure 5 Particle size change curve of G-Exos during storage at -80°C for 8 weeks.
[0028] Figure 6 TEM images and SEM images of PDA@PEG nanoparticles.
[0029] Figure 7 Hydrodynamic size and Zeta potential distribution of PDA@PEG.
[0030] Figure 8 Particle size change curve of PDA@PEG nanoparticles during 60 days storage at 25 °C.
[0031] Figure 9 Protective effects of G-Exos and PDA@PEG on H2O2-induced HaCaT and PIG1 cell viability.
[0032] Figure 10 ROS scavenging effects of each treatment group on PIG1 cells.
[0033] Figure 11 Effects of each treatment group on SOD, CAT activities and MDA content in H2O2-damaged HaCaT cells.
[0034] Figure 12 Inhibitory effects of each treatment group on LPS-induced TNF-α and IL-6 secretion of HaCaT cells.
[0035] Figure 13 PIG1 cell uptake of PDA@PEG nanoparticles.
[0036] Figure 14 Ultrastructure observation of PDA@PEG nanoparticle distribution in PIG1 cells.
[0037] Figure 15 Promoting effects of G-Exos and PDA@PEG on PIG1 cell melanin synthesis.
[0038] Figure 16 TEM images of G-Exos@TM composite micelles.
[0039] Figure 17 Particle size and Zeta potential comparison of G-Exos, TM and G-Exos@TM composite micelles.
[0040] Figure 18 Particle size change and G-Exos cumulative release curve of G-Exos@TM composite micelles during incubation in PBS with / without MMP-9.
[0041] Figure 19 Stereo microscope overall morphology and SEM images of composite microneedle patches.
[0042] Figure 20 Force-displacement curve of the composite microneedle.
[0043] Figure 21 H&E staining section of mouse skin after treatment with the composite microneedle patch.
[0044] Figure 22 Optical microscope images of the swelling process of the composite microneedle patch in PBS (pH 7.4).
[0045] Figure 23 In vitro release curves of PDA@PEG and G-Exos in the composite microneedle patch in PBS with / without MMP-9.
[0046] Figure 24 Cytotoxicity evaluation of the composite microneedle extract on PIG1 and HaCaT cells.
[0047] Figure 25 Macroscopic repigmentation photographs of the back of vitiligo model mice in each group after different treatment periods, vitiligo scores, and quantitative analysis of the back repigmentation area.
[0048] Figure 26 H&E staining sections and quantitative analysis of the dermal thickness of the back skin tissue of mice in each group.
[0049] Figure 27 Masson-Fontana staining sections of the back skin tissue of mice in each group.
[0050] Figure 28 Confocal microscope images and quantitative analysis of the ROS level in the skin tissue of mice in each group.
[0051] Figure 29 Determination results of SOD, CAT activity, and MDA content in the skin tissue of mice in each group.
[0052] Figure 30 Immunohistochemical staining images and quantitative analysis of TNF-α expression in the skin tissue of mice in each group.
[0053] Figure 31 ELISA determination results of TNF-α and IL-6 concentrations in the skin tissue homogenate of mice in each group. DETAILED DESCRIPTION
[0054] In order to further understand the present application, the technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0055] Unless otherwise specified, the reagents involved in the embodiments of the present application are all commercially available products, which can be purchased through commercial channels.
[0056] Example 1: Extraction and purification of ginseng root-derived exosomes (G-Exos) Step 1: Pre-treatment of tissue Step 1.1: Fresh ginseng root tissue was taken and placed in pre-cooled 0.01 M phosphate buffer solution (PBS, pH 7.4), and gently stirred with a glass rod. The surface was washed repeatedly for 3 times to completely remove the dirt and impurities on the surface. The excess liquid on the surface of the tissue was absorbed with sterile filter paper, and then the ginseng root tissue was cut into small pieces with a volume of 1-2 cm 3 using a sterile scalpel.
[0057] Step 1.2: 10 g of the cut ginseng tissue was accurately weighed and placed in a 200 mL high-speed tissue homogenizer, and 30 mL of pre-cooled PBS buffer was added at a mass-volume ratio of 1:3.
[0058] Step 2: Tissue homogenization and coarse filtration The homogenization cup containing the mixture was placed in an ice water bath, and the high-speed tissue homogenizer was used at a speed of 15,000 rpm for 60 seconds each time. After each homogenization, the system was cooled for 30 seconds, and the process was repeated for 3 times until the tissue was completely broken, obtaining a tissue homogenate. The tissue homogenate was poured into a 200-mesh stainless steel sieve, and a glass rod was used to guide the collection of the filtrate. Further filtration was performed through four layers of sterile gauze to remove residual fibrous impurities, and the final filtrate was collected.
[0059] Step 3: Fractionated centrifugation Step 3.1: The filtrate obtained in step 2 was divided into 50 mL ultracentrifuge tubes and centrifuged at 2,000 ×g for 20 minutes at 4°C using a high-speed refrigerated centrifuge.
[0060] Step 3.2: After centrifugation, the supernatant was carefully aspirated without touching the precipitate at the bottom of the tube, and the collected supernatant was labeled as "supernatant A". The supernatant A was transferred to a new ultracentrifuge tube and centrifuged at 10,000 ×g for 60 minutes at 4°C.
[0061] Step 3.3: After centrifugation, the supernatant was also carefully aspirated without touching the precipitate at the bottom of the tube, and the collected supernatant was labeled as "supernatant B".
[0062] Step 4: Preliminary enrichment of exosomes by ultracentrifugation The supernatant B was filtered through a 0.45 μm water phase polyether sulfone needle filter to remove the possible remaining micro-sized vesicles and impurities. The filtered supernatant was transferred into a centrifuge tube for ultracentrifugation, and an ultracentrifuge was used to centrifuge at an average relative centrifugal force of 120,000 x g for 2 hours at 4 °C. After centrifugation, the supernatant was slowly poured out and completely discarded, and a layer of light yellow film-shaped precipitate was observed at the bottom of the tube, which was the crude exosome.
[0063] Step 5: Purification by sucrose density gradient centrifugation The precipitate obtained in step 4 was gently resuspended with 1 mL of pre-cooled PBS buffer, avoiding violent blowing, to obtain a crude exosome suspension. In the ultracentrifuge tube, 3 mL of 60%, 45%, 30%, and 8% (w / v) sucrose solutions were sequentially and slowly added from bottom to top to form a discontinuous sucrose density gradient. The 1 mL crude exosome suspension obtained in step 4 was carefully added to the top of the sucrose density gradient liquid using a Pasteur pipette. The gradient centrifuge tube was placed in the horizontal rotor of the ultracentrifuge, and centrifugation was performed at 120,000 x g at 4 °C for 90 minutes. After centrifugation, the centrifuge tube was carefully removed, and a cream-colored to milk-yellow band was observed at the interface between the 30% and 45% sucrose solutions. A 1 mL sterile syringe with a needle was used to carefully suck the band at the interface, and a high-purity G-Exos solution was collected.
[0064] Step 6: Purification by ultracentrifugation and storage The collected sucrose density gradient centrifuged solution containing G-Exos was transferred to a suitable ultracentrifuge tube. An ultracentrifuge was used to centrifuge at 120,000 x g at 4 °C for 70-90 minutes. The supernatant was carefully discarded, and a visible yellowish or cream-colored precipitate should be present at the bottom of the tube. An appropriate amount of pre-cooled PBS buffer was added to the centrifuge tube containing the G-Exos precipitate, and the tube was gently blown or repeatedly washed with a pipette gun at the bottom to ensure that the precipitate was fully and gently resuspended. The resuspended solution was allowed to stand at 4 °C for 1 hour to help dissolution. The protein concentration of the G-Exos resuspended solution was determined using a BCA protein quantification kit according to the instructions. The solution was diluted with PBS buffer to a final protein concentration of 2.0 mg / mL. The diluted G-Exos solution was aliquoted at 50 μL / tube and stored in a -80 °C ultra-low temperature freezer for long-term storage.
[0065] Example 2: Preparation of enzyme-responsive complex micelles (G-Exos@TM) Accurately weigh 10.0 mg of TM into a 5 mL clean glass sample bottle, and use a pipette to accurately add 1.0 mL of ultrapure water into the sample bottle. Place the sample bottle in a constant temperature water bath at 60°C for heating, and use an ultrasonic cell disruptor for ultrasonic-assisted dissolution. Set the ultrasonic power to 100 W, and the working mode to 2 seconds of work and 3 seconds of interval. Continue to treat until the TM is completely dissolved, and the solution is clear and transparent, to obtain a TM pre-dispersion solution, which is ready for use.
[0066] Step 2: Mixing and emulsification of exosomes and micelles Step 2.1: Accurately weigh 1.0 mL of G-Exos prepared in Example 1, with a protein concentration of 2.0 mg / mL.
[0067] Step 2.2: Place the TM pre-dispersion solution on a magnetic stirrer, and maintain the system temperature at 60°C, with constant stirring at a speed of 500 rpm.
[0068] Step 2.3: Use a micro-injection pump to slowly and uniformly drop the G-Exos solution weighed in Step 2.1 into the continuously stirred TM pre-dispersion solution at a constant flow rate of 1.0 mL / min.
[0069] Step 2.4: After the dropping is completed, continue to maintain the 60°C water bath and 500 rpm stirring conditions for 30 minutes, to allow the G-Exos and TM molecules to fully interact with each other.
[0070] Step 2.5: Quickly transfer the above mixed solution to an ice-water bath, and cool to 0-4°C.
[0071] Step 2.6: Use the same probe sonicator (set the power to 200 W, and the pulse mode to 2 seconds of work and 3 seconds of interval) to ultrasonically treat the mixed solution under ice bath conditions, for a total treatment time of 5 minutes, to complete the emulsification and drug loading process, and form the primary composite micelles.
[0072] Step 3: Dialysis purification and product collection Step 3.1: Transfer the primary composite micelle solution after ultrasonic treatment into a regenerated cellulose dialysis bag with a molecular weight cut-off of 3,500 Da, and ensure that the dialysis bag is tightly sealed at both ends. Completely immerse the dialysis bag in 2.0 L of phosphate buffer solution (PBS, 0.01 M, pH 7.4) in a 4°C cold room or refrigerator, and slowly stir the dialysis solution using a magnetic stirrer. Continue the dialysis purification process for 24 hours, and completely replace the dialysis solution (2.0 L of PBS each time) every 4 hours during the process.
[0073] Step 3.2: After dialysis, the final solution was carefully collected from the dialysis bag, which was the purified enzyme-responsive composite micelles loaded with ginseng root-derived exosomes (G-Exos@TM) solution. The obtained G-Exos@TM solution was aliquoted in brown sample bottles and stored at 4 °C in the dark for later use.
[0074] Example 3: Synthesis of polydopamine-polyethylene glycol nanoparticles (PDA@PEG) Step 1: Synthesis of polydopamine nanoparticles Step 1.1: 360 mg of dopamine hydrochloride was accurately weighed and placed in a 250 mL three-necked round-bottom flask. 180 mL of deionized water was added, and the mixture was lightly shaken to achieve initial dispersion.
[0075] Step 1.2: The three-necked flask was placed in a 50 °C constant-temperature water bath, a mechanical stirrer was installed, and stirring was performed at a constant speed of 800 rpm until the dopamine hydrochloride was completely dissolved, resulting in a colorless transparent solution.
[0076] Step 1.3: A constant-flow pump or microsyringe pump was used to slowly and uniformly add 1.52 mL of 1 M sodium hydroxide solution to the above solution at a rate of 0.05 mL / min.
[0077] Step 1.4: After the addition was complete, the 50 °C water bath and 800 rpm stirring speed were maintained for 5 hours of continuous reaction. During this process, it was observed that the color of the reaction system changed from colorless to light brown, dark brown, and finally dark black, indicating that polydopamine nanoparticles had been formed.
[0078] Step 1.5: After the reaction was complete, the reaction solution was transferred to a centrifuge tube, and a high-speed centrifuge was used to centrifuge at 12,000 ×g for 10 minutes at room temperature. The supernatant was carefully discarded, and the black precipitate at the bottom was collected.
[0079] Step 1.6: 50 mL of deionized water was added to the precipitate, which was completely resuspended using a vortex shaker for 1 minute. The mixture was then centrifuged again at 12,000 ×g for 10 minutes, and the supernatant was discarded. This washing process was repeated three times to ensure complete removal of unreacted monomers and byproducts.
[0080] Step 1.7: The final washed polydopamine nanoparticle precipitate was resuspended in 5 mL of deionized water to obtain a preliminary purified PDA nanoparticle dispersion, which was ready for use.
[0081] Step 2: PEGylation modification and final purification Step 2.1: 100 mg of methoxy-polyethylene glycol-amine was accurately weighed and added to the 5 mL PDA nanoparticle dispersion prepared in Step 1.
[0082] Step 2.2: The mixed solution was placed in an ice water bath, and a probe ultrasonic instrument was used to treat it in pulse mode with power of 300 W, working for 2 seconds / interval of 3 seconds, for a total of 40 minutes, to promote the physical adsorption and initial combination of mPEG-NH2 and the surface of PDA particles.
[0083] Step 2.3: After ultrasonic treatment, the ice bath was removed, and the reaction solution was placed on a magnetic stirrer for stirring at a speed of 400 rpm for 12 hours at room temperature (25±2°C), so that the mPEG-NH2 was covalently grafted to the surface of the PDA nanoparticles through Michael addition or Schiff base reaction.
[0084] Step 2.4: The solution after the reaction was completely transferred to a regenerated cellulose dialysis bag with a molecular weight cut-off of 8-14 kDa.
[0085] Step 2.5: The dialysis bag was placed in a 2 L beaker and dialyzed and purified using deionized water for a total of 48 hours. During this period, the dialysate was replaced every 6 hours, and each time 2 L of fresh deionized water was used to ensure complete removal of unreacted mPEG-NH2 molecules.
[0086] Step 2.6: After the dialysis was completed, the dark black solution in the dialysis bag was collected, and the purified polydopamine-polyethylene glycol nanoparticle solution was obtained. It can be sterile filtered through a 0.22 μm microporous filter and stored in a dark environment at 4°C for standby use (see reaction schematic diagram in Figure 1 ).
[0087] Example 4: Hyaluronic acid microneedle patch loaded with G-Exos@TM and PDA@PEG and a preparation method thereof Step 1: Preparation of composite microneedle tip matrix solution Step 1.1: The following components were accurately weighed and placed in a 2 mL brown screw thread glass sample bottle to avoid light-induced pre-crosslinking: Methacrylated hyaluronic acid (HAMA): 50.0 mg; polyvinyl alcohol (PVA, alcoholysis degree 87-89%, Mw 31,000-50,000): 10.0 mg; light initiator LAP: 1.0 mg Step 1.2: 1.0 mL of deionized water was accurately measured using a pipette and added to the above sample bottle.
[0088] Step 1.3: Immediately tighten the bottle cap and place it on a vortex shaker for oscillation at a speed of 2500 rpm for 3 minutes to initially wet and disperse the powder.
[0089] Step 1.4: Subsequently, the sample bottle was transferred to a 37°C constant temperature shaker and shaken at 150 rpm for 20 minutes until all components were completely dissolved to obtain a clear, transparent, and uniform microneedle base solution.
[0090] Step 1.5: The following two active ingredient solutions were accurately measured in sequence: Example 2: G-Exos@TM composite micelle solution 100 μL (0.2 mg of G-Exos protein mass was loaded).
[0091] Example 3: PDA@PEG nanoparticle solution 50 μL (1.0 mg of nanoparticle dry weight was loaded).
[0092] Step 1.6: Using a 100-1000 μL adjustable pipette, the above two active ingredient solutions were slowly added to the microneedle base solution prepared in step 1.4 in sequence.
[0093] Step 1.7: Using the same pipette, set the volume to 500 μL, slowly pipette the mixed solution 15 times, the operation should be gentle to ensure that the two active ingredients are uniformly dispersed in the matrix, while avoiding the introduction of air bubbles as much as possible.
[0094] Step 1.8: Finally, a homogeneous, double active ingredient-loaded microneedle tip matrix solution was obtained, which was placed in a light-tight container and stored at room temperature in the dark until use, and the subsequent molding steps should be completed within 1 hour.
[0095] Step 2: Molding and preparation of microneedle patches Step 2.1: The polydimethylsiloxane (PDMS) microneedle mold was treated for hydrophilicity using an oxygen plasma treatment machine. The mold specifications were 10x10 array, conical needle body, needle height 750 μm, needle base diameter 500 μm, and needle tip center-to-center distance 500 μm. The treatment parameters were set as follows: power 100 W, treatment time 60 seconds.
[0096] Step 2.2: The composite microneedle tip matrix solution prepared in step 1 was uniformly and continuously added to the surface of the PDMS mold treated by plasma using a pipette, ensuring that the liquid surface completely covered and was slightly higher than all the needle tip cavities.
[0097] Step 2.3: The mold was smoothly placed in the rotor of a table centrifuge, and centrifuged at a relative centrifugal force of 2,000 xg for 10 minutes at room temperature (25 ± 2°C) to allow the needle tip matrix solution to fully fill and fill each needle tip cavity under the driving force of centrifugation.
[0098] Step 2.4: Immediately after centrifugation, use a disposable plastic spatula to scrape the surface of the mold at an angle of about 45 degrees, unidirectionally and smoothly, to completely remove the excess solution on the surface, ensuring that only the needle tip cavity retains sufficient amount of the matrix solution.
[0099] Step 2.5: After treatment, move the mold horizontally into a 37°C drying oven for 2 hours of pre-drying, to preliminarily shape and concentrate the needle tip structure.
[0100] Step 2.6: After pre-drying, place the mold on the workbench of the 405 nm wavelength UV crosslinking instrument. Adjust the UV light intensity to 15 mW / cm 2 , ensure that the light path is perpendicular to the surface of the mold, and irradiate for 60 seconds to allow the HAMA molecules to undergo sufficient photo-crosslinking reaction and form a stable hydrogel network structure.
[0101] Step 2.7: Accurately weigh 4.0 g of polyvinyl alcohol (PVA, same specifications as above) powder, dissolve in 20 mL of deionized water to prepare a 20% (w / v) PVA aqueous solution. Place the solution in a 60°C water bath and stir at 200 rpm until completely dissolved and clear, to obtain a microneedle backing layer solution.
[0102] Step 2.8: Add the PVA backing solution prepared in step 2.7 to the base portion of the mold with the solidified needle tip structure, and the droplet volume should just completely cover the base area (about 1-2 mm thick) without overflowing to the needle tip portion.
[0103] Step 2.9: Move the mold to the 37°C drying oven again for continuous drying for 48 hours, to completely evaporate the water in the backing layer and solidify to form a flexible support layer, which is firmly physically combined with the needle tip layer.
[0104] Step 2.10: After drying is complete, carefully and completely remove the microneedle patch from the edge of the mold using flat tweezers. Use a dust-free paper to wipe off any possible burrs on the back of the patch.
[0105] Step 2.11: Place each prepared microneedle patch in an aluminum foil bag for vacuum packaging. Store the final product in a dry, dark, and dry environment at 4°C (see Figure 2 for a schematic diagram of synthesis and release).
[0106] Test Example 1: Structural characterization of ginseng root-derived exosomes (G-Exos) 1. Extraction efficiency and morphological observation To verify the efficiency of the extraction method (see Example 1) and the morphology of the product, the following experiments were performed: Step 1.1: Extraction Efficiency Calculation. 1.0 kg of fresh ginseng rhizome was accurately weighed, and the procedure was strictly followed according to Example 1 to obtain a purified G-Exos solution. The protein concentration of the obtained G-Exos solution was determined using a BCA protein quantification kit, following the manufacturer's instructions. After three independent replicate experiments and averaging the results, the calculated amount of G-Exos protein that could be stably obtained from each kg of fresh ginseng rhizome was 50.0 ± 3.5 mg.
[0107] Step 1.2: Morphological observation using transmission electron microscopy. Take 10 μL of the above G-Exos solution (protein concentration approximately 0.1 mg / mL) and drop it onto the copper grid of the carbon support membrane, allowing it to stand for 3 minutes to absorb. Blot away excess liquid from the edges with filter paper, then add 10 μL of 2% (w / v) phosphotungstic acid solution (pH 7.0) for negative staining, and blot dry with filter paper after 1 minute. Observe the prepared sample under a JEM-1400Flash transmission electron microscope with an accelerating voltage set to 80 kV. Results are as follows: Figure 3 As shown, the G-Exos observed in the field of view exhibits a typical exosome sac-like or cup-shaped morphology, with an intact structure and good dispersion throughout the field of view. No obvious aggregates were observed, indicating that the G-Exos sample prepared in this invention has high purity.
[0108] 2. Particle size distribution and stability analysis To characterize the physical properties and storage stability of G-Exos, the following analysis was performed: Step 2.1: Particle size and polydispersity index determination. The G-Exos solution was diluted with sterile PBS to a suitable detection concentration (protein concentration approximately 0.05 mg / mL). Measurements were performed using a Malvern Zetasizer Nano ZS90 dynamic light scattering instrument, with the detection temperature set at 25°C and the equilibration time at 60 seconds. The results showed that the main peak distribution of the hydrodynamic diameter of G-Exos was 137.1 ± 11.4 nm (…). Figure 4 A). Its polydispersity index is 0.15±0.03, which is less than 0.2, indicating that the sample particle size has a narrow unimodal distribution and the system is highly homogeneous.
[0109] Step 2.2: Zeta potential measurement. Using the same instrument, laser Doppler electrophoresis was performed to measure the Zeta potential of the original concentration G-Exos solution at 25°C. After three repeated measurements, the average Zeta potential value was -21.29 ± 0.51 mV. Figure 4 B). The relatively high absolute value of the negative charge (generally considered to be greater than 20 mV) confirms that G-Exos has good colloidal stability in aqueous media due to the electrostatic repulsion between particles, and is not prone to aggregation.
[0110] Step 2.3: Storage stability evaluation. The same batch of prepared G-Exos solution was aliquoted and stored in -80 °C ultra-low temperature freezer. After 2 months of storage, one aliquot was taken out and the particle size distribution was measured again according to the method of Step 2.1. The results showed that the particle size peak of the sample after storage did not shift significantly (Figure 2.3). Figure 5 This result proved that the G-Exos prepared according to the method of the present application could maintain its colloidal stability for a long time under the condition of -80 °C.
[0111] Test Example 2: Synthesis and characterization of polyethylene glycol modified polydopamine nanoparticles (PDA@PEG) 1. Synthesis of PDA@PEG nanoparticles Step 1.1: Synthesis and purification. The polydopamine nanoparticle dispersion was successfully obtained by oxidative polymerization of dopamine hydrochloride under alkaline conditions and subsequent centrifugal purification according to the method described in Example 3.
[0112] Step 1.2: Surface modification. mPEG5000-NH2 was added to the PDA dispersion obtained in the previous step, and the PEG chain was stably covalently linked to the PDA core by Schiff base / Michael addition reaction through ice bath ultrasonic assisted dispersion and continuous stirring at room temperature.
[0113] Step 1.3: Final purification. The unreacted mPEG-NH2 was removed by dialysis, and the purified PDA@PEG nanoparticle solution was finally obtained for subsequent characterization and biological evaluation.
[0114] 2. Characterization of the physical and chemical properties of PDA@PEG nanoparticles Step 2.1: Morphological observation. 10 μL of PDA@PEG solution (diluted by an appropriate multiple) was added to a carbon-supported copper mesh, and after natural air-drying, it was observed by transmission electron microscopy (TEM) Figure 6 A) and scanning electron microscopy (SEM) Figure 6 B). The images showed that the obtained nanoparticles were monodisperse spherical in shape.
[0115] Step 2.2: Particle size determination. The average diameter of PDA@PEG nanoparticles was measured by counting at least 200 particles in the transmission electron microscopy images, which was 162 ± 4.3 nm (A). Figure 7
[0116] Step 2.3: Zeta potential determination. The PDA@PEG solution was diluted to an appropriate concentration with deionized water, and a nanoparticle size and Zeta potential analyzer was used for determination. The results showed that the Zeta potential was -19.72 ± 0.51 mV (Figure 7 B).
[0117] Step 2.4: Stability evaluation. The PDA@PEG solution was stored at 25°C for 60 days, during which its particle size was determined by dynamic light scattering method periodically, no significant aggregation or precipitation was observed (Fig. 2B), demonstrating its good long-term stability. Figure 8
[0118] Test Example 3: Evaluation of synergistic therapeutic effect of G-Exos and PDA@PEG 1. Evaluation of synergistic cytoprotective effect Step 1.1: Cell culture. Human immortalized keratinocytes (HaCaT) were cultured in DMEM medium (Gibco) supplemented with 10% fetal bovine serum (FBS, BI) and 1% penicillin / streptomycin (100 U / mL). Human immortalized melanocytes (PIG1) were cultured in Medium 254 (Gibco) supplemented with 5% fetal bovine serum, 1% penicillin / streptomycin and 10% HMGS-2 (Gibco). All cells were cultured at 37°C, 5% CO2.
[0119] Step 1.2: Cell grouping treatment. HaCaT and PIG1 cells were cultured according to the method described in step 1.1, and seeded in 96-well plates at a density of 1×10 4 cells per well. After 24 hours of adhesion, the culture medium was replaced with one containing 0.8 mmol / L H2O2 to establish an oxidative stress model, and immediately subjected to the following grouping intervention: ① control group; ② G-Exos group (10 μg / mL); ③ PDA@PEG group (50 μg / mL); ④ combined treatment group (10 μg / mL G-Exos + 50 μg / mL PDA@PEG).
[0120] Step 1.3: Cell viability detection. After 24 hours of intervention, cell viability was detected by CCK-8 method. The results showed that compared with single treatment groups, the combined treatment of G-Exos and PDA@PEG could more significantly reverse the H2O2-induced toxicity of HaCaT ( Figure 9 A) and PIG1 cells ( Figure 9 B).
[0121] 2. Evaluation of synergistic antioxidant effect Step 2.1: Intracellular reactive oxygen species (ROS) level detection. PIG1 cells were seeded at the same density and treated with fresh culture medium containing various formulations for 4 hours (grouping step 1.2). After treatment, the culture medium was discarded and serum-free medium containing 10 mM DCFH-DA probe was added for 30 minutes incubation at 37 °C. Subsequently, the cells were washed twice with PBS and morphological observation was performed by fluorescence microscopy (Olympus BX51, Japan) with a 40x objective lens. Figure 10 The results showed that G-Exos was a more effective intracellular ROS scavenger than PDA@PEG, while the combination treatment group showed the greatest signal attenuation, indicating a synergistic scavenging effect.
[0122] Step 2.2: Endogenous antioxidant system and oxidative damage detection. After pre-treatment of HaCaT cells with 0.8 mmol / L H2O2 for 4 hours, the medium was replaced with medium containing different formulations for further incubation for 24 hours (grouping step 1.2). The cells were collected and the activities of superoxide dismutase (SOD) and catalase (CAT) and the content of malondialdehyde (MDA) were determined using commercial kits. The results ( Figure 11 ) showed that G-Exos could significantly restore SOD and CAT activities and reduce MDA levels (p < 0.01 compared with the PDA@PEG group), and this effect was further amplified in the combination group (p < 0.001).
[0123] 3. Evaluation of synergistic anti-inflammatory effect Step 3.1: Inflammatory cytokine determination. HaCaT cells were seeded at an appropriate density and stimulated with 0.1 ng / mL lipopolysaccharide (LPS) for 24 hours to establish an inflammation model, while grouping intervention was performed (grouping step 1.2). After incubation, the cell culture supernatant was collected and the concentrations of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were determined using ELISA kits. The results ( Figure 12 ) showed that G-Exos alone could inhibit the secretion of TNF-α and IL-6 by 62% and 57%, respectively, while the combination treatment further strengthened this inhibitory effect, indicating a synergistic anti-inflammatory effect.
[0124] 4. Cell uptake and ultrastructure analysis of PDA@PEG Step 4.1: Confocal microscopy observation. PIG1 cells were seeded in 15 mm glass bottom confocal culture dishes and co-incubated with 50 pg / mL PDA@PEG for 24 hours. Subsequently, the cells were fixed with 4% paraformaldehyde, stained with rhodamine-phalloidin for cytoskeletal fibrous actin (red fluorescence), and counterstained with DAPI for the cell nucleus (blue fluorescence). The overlay images of bright field and fluorescence channels ( Figure 13) shows that PDA@PEG (dark particles under bright field) is present in large amount in cytoplasm and the cell morphology remains intact.
[0125] Step 4.2: Transmission electron microscopy observation. PIG1 cells treated with PDA@PEG were prepared routinely: first fixed with 2.5% glutaraldehyde at 4°C overnight, then post-fixed with 1% osmium tetroxide. Subsequently dehydrated through an ethanol-acetone gradient series, infiltrated with acetone-epoxy resin mixture, and finally heat polymerized (35°C to 80°C). Ultrathin sections of 70-90 nm were prepared using an ultramicrotome (Leica EM UC7), and observed under transmission electron microscope after staining with uranyl acetate and lead citrate. Results Figure 14 ) clearly show the distribution of PDA@PEG nanoparticles in intracellular vesicles and cytoplasmic compartments, confirming their efficient internalization.
[0126] 5. Synergistic promotion of melanin synthesis Step 5.1: Quantitative analysis of melanin content. PIG1 cells were seeded in 6-well plates and cultured overnight before grouping intervention (grouping step 1.2) for 24 hours. After treatment, the culture medium was discarded, the cells were washed with PBS, and the cell precipitate was collected. 100 μL of 1 M sodium hydroxide solution was added to the precipitate, which was incubated at 80°C water bath for 1 hour to fully dissolve the melanin. After cooling, the absorbance value of the solution was measured at 490 nm wavelength using a microplate reader to quantify the melanin content. Results Figure 15 ) show that PDA@PEG monotherapy can significantly increase melanin synthesis (1.32-fold increase, p < 0.05) compared to the H2O2-damaged model group, while the G-Exos / PDA@PEG combination further increases melanin production to 1.41-fold (p < 0.01).
[0127] Test Example 4: Preparation, characterization and enzyme-responsive release study of G-Exos@TM complex micelles 1. Preparation of G-Exos@TM complex micelles G-Exos@TM complex micelles were prepared according to the method described in Example 2. Briefly, uniform G-Exos@TM complex micelle solution was obtained by mixing glycerol monostearate (TM) aqueous solution with G-Exos solution, ultrasonic emulsification in ice bath and dialysis purification.
[0128] 2. Physicochemical characterization of G-Exos@TM complex micelles Step 2.1: Morphological observation. 10 μL of G-Exos@TM solution was added to a copper grid on a carbon-supported membrane. After standing for 3 minutes to absorb the adsorption, excess liquid was blotted away with filter paper. Then, 2% phosphotungstic acid solution was added for negative staining for 1 minute. Under a transmission electron microscope, vesicle-like structures were clearly surrounded by a membrane. Figure 16 ), consistent with the micellar encapsulation structure.
[0129] Step 2.2: Particle size and Zeta potential analysis. An appropriate amount of G-Exos@TM composite micelle solution was diluted with PBS and then measured using a nanoparticle size and Zeta potential analyzer. The results showed that the hydrodynamic diameter of G-Exos@TM was 182.7 ± 19 nm. Figure 17 A), the diameter of unmodified G-Exos is 144.7 ± 15 nm ( Figure 17 B). The zeta potential of TM itself is -1.6 ± 0.2 mV, the zeta potential of unmodified G-Exos is -26.6 ± 2.2 mV, and the zeta potential of G-Exos@TM is -11.2 ± 1.2 mV. Figure 17 C).
[0130] 3. Evaluation of enzyme response and release characteristics Step 3.1: In vitro release experiment design. The newly prepared G-Exos@TM complex was diluted with the following two media: Group A: PBS (pH 7.4); Group B: PBS (pH 7.4) containing 1 ng / mL MMP-9.
[0131] All samples were placed in a 37°C constant temperature shaker and continuously oscillated at 600 rpm.
[0132] Step 3.2: Particle size change monitoring. Samples were taken daily from each group, and the hydrodynamic diameter changes of the particles were monitored using dynamic light scattering. The results showed ( Figure 18 A): In the presence of MMP-9, the particle size recovered to the size of the natural G-Exos after 7 days; while in PBS without MMP-9, the particle size only decreased slightly to about 170 nm.
[0133] Step 3.3: Quantitative analysis of exosome release. Samples were taken from both groups at specified time points (days 1, 3, and 7), centrifuged, and resuspended. The amount of G-Exos released was quantified by detecting the exposure level of the exosome surface marker CD63 using the TINGO exosome ELISA kit, following the instructions. Results showed ( Figure 18B): In PBS, only less than 7% of G-Exos was released from the complex within 7 days, and almost all of the G-Exos was released in the presence of MMP-9 at the 7th day.
[0134] Test Example 5: Preparation, performance evaluation and in vitro release study of composite microneedle patch 1. Preparation of composite microneedle patch The composite microneedle patch loaded with G-Exos@TM and PDA@PEG was prepared according to the method described in Example 4. Briefly, G-Exos@TM complex micelles were blended with PDA@PEG nanoparticles in the HAMA precursor solution, and after injection into the PDMS mold, they were filled by centrifugation, pre-dried, cross-linked by UV light, and finally a PVA backing layer was added and demolded to obtain a complete composite microneedle patch.
[0135] 2. Morphology and structure characterization of microneedle Step 2.1: Stereomicroscope observation. The overall morphology of HAMA / G-Exos@TM / PDA@PEG composite microneedle was observed by stereomicroscope, and the results showed that the needle array was arranged in order (Fig. 2A). Figure 19 A).
[0136] Step 2.2: Morphological observation. The dried microneedle patch was fixed on the sample stage, and after gold spraying treatment, it was observed by scanning electron microscope. The SEM image showed (Fig. 2B) that the microneedle was regular conical, the needle tip was sharp, the size was uniform, the needle height was 750 μm, and the base diameter was 500 μm. Figure 19 B).
[0137] 3. Mechanical property and skin penetration ability evaluation Step 3.1: Mechanical strength test. Displacement-force testing system was used, equipped with a 50 kg load sensor. The microneedle tip was vertically fixed on a stainless steel platform, and the sensor was lowered from 1 cm above the needle tip at a speed of 0.1 mm / s. After contact, the speed was reduced to 0.01 mm / s, and the loading continued until the displacement reached 800 μm. The force-displacement curve was recorded. The results showed (Fig. 3A): the breaking force of HAMA / G-Exos@TM / PDA@PEG microneedle was 0.13 N / needle, which was higher than the minimum force required for skin insertion. Figure 20
[0138] Step 3.2: In vitro skin penetration experiment. Full-thickness mouse skin was taken and fixed on the experimental platform after removing the subcutaneous fat. The microneedle patch was vertically placed on the skin surface, and the thumb pressure was applied for 10 minutes. After removal, the skin sample was fixed with 4% paraformaldehyde, embedded in paraffin and sectioned, and then stained with H&E. The histological section confirmed that the microneedle channel completely penetrated the stratum corneum (Fig. 3B), indicating that the microneedle had good skin penetration ability. Figure 21
[0139] 4. Swelling and drug release behavior study Step 4.1: Swelling behavior test. The microneedle patches were immersed in PBS (pH 7.4) at 37 °C, and morphological changes were observed by digital optical microscope at timed intervals. The results showed that the microneedles rapidly absorbed water and swelled, and the structure disintegrated over time, with the morphology collapsing substantially after 15 minutes. This swelling behavior is crucial for promoting sustained transdermal release of drugs in the hydrogel matrix. Figure 22
[0140] Step 4.2: Drug release curve determination. The microneedle patches were placed in PBS containing 1 ng / mL MMP-9 and PBS without MMP-9, respectively, and gently shaken at 37 °C. The release medium was collected at different time points and quantitatively analyzed by the following methods: PDA@PEG nanoparticles: measuring their characteristic absorbance at 280 nm G-Exos: detecting the CD63 surface marker using the TINGO exosome ELISA kit Step 4.3: Release property analysis. The release curves showed that PDA@PEG was rapidly released up to 98.4% in both PBS and MMP-9 solution within 2 hours, exhibiting a burst release mode (A); the release of G-Exos showed enzyme-triggered characteristics: in the presence of MMP-9, the cumulative release rates on the 3rd and 7th days were 71.3% and 99.4%, respectively; while in PBS without MMP-9, the release rates during the same period were only 18.5% and 38.2% (B). Figure 23 Figure 23
[0141] 5. Biocompatibility evaluation Step 5.1: Cytotoxicity test. The microneedle extracts were co-cultured with P1G1 and HaCaT cells for 24 hours, and cell viability was detected by the CCK-8 method. The results showed no significant toxicity difference compared with the untreated control group (Fig. 5). Figure 24
[0142] Test Example 6: Evaluation of the therapeutic effect of composite microneedle patches in a vitiligo animal model 1. Animal model establishment and experimental design Step 1.1: Establishment of a vitiligo model. Female C57BL / 6 mice aged 4-6 weeks were selected, and after being anesthetized by intraperitoneal injection of 5% chloral hydrate (350 mg / kg), an external emulsion containing 33.3% vaseline, 50% 4-benzyloxyphenol, and 16.7% tretinoin was evenly applied to the depilation area, once every other day, for 30 days, to establish a stable vitiligo model. This treatment induced selective hair follicle melanin loss while maintaining epidermal integrity, closely simulating the pathology of human vitiligo.
[0143] Step 1.2: Experimental grouping and treatment. The successfully modeled mice were randomly divided into 5 groups (n=5): ① Model group; ② HAMA microneedle group (empty microneedle); ③ HAMA / G-Exos@TM microneedle group; ④ HAMA / PDA@PEG microneedle group; ⑤ HAMA / G-Exos@TM / PDA@PEG microneedle group. From the 30th day of modeling, the corresponding microneedle patches were placed in the center of the depigmented area, and replaced every 3 days for 3 weeks.
[0144] 2. Macroscopic evaluation of treatment effect Step 2.1: Observation of repigmentation process. Back photos were taken every week to record the changes in hair depigmentation. The results showed (A): Figure 25 Week 1: The combined treatment group showed significant hair repigmentation in the application area, better than the other groups; Week 2: The combined treatment group's repigmentation advantage was further strengthened; Week 3: The combined treatment group achieved nearly complete repigmentation, and the empty microneedle group also induced about 20% repigmentation.
[0145] Step 2.2: Vitiligo score. Score according to the percentage of depigmented area (0-5 points). The results showed (B) that all groups had an initial score of >4 points (>50% back depigmentation); the control group remained about 4 points throughout; the combined treatment group's score improved gradually: to about 2 points in the 2nd week, and further to 1 point in the 3rd week. Figure 25
[0146] Step 2.3: Quantitative analysis of repigmentation area. ImageJ quantitative analysis showed (C) that the combined treatment group had significantly increased repigmentation surface area compared to the model control group (p < 0.001) at week 3. Figure 25
[0147] 3. Histological analysis Step 3.1: Sample processing. After the last treatment, back skin was taken, fixed with 4% formalin, paraffin-embedded, and sections were prepared.
[0148] Step 3.2: H&E staining analysis. The results showed (A): Figure 26 ): The combined treatment group had significantly increased hair follicle density, with hair follicles mainly in the late anagen phase; the single-drug treatment groups had increased hair follicle numbers, but mainly stalled in the early anagen phase. Dermis thickness measurement showed that the combined treatment achieved maximum dermis thickness (p < 0.01).
[0149] Step 3.3: Masson-Fontana staining analysis. The results showed (B): Figure 27 ): All microneedle treatment groups showed enhanced melanin synthesis and developing hair bulbs within the hair follicles; the combined treatment group showed an extended lower half of the hair follicle and maximum melanin content; the control group maintained a sparse hair follicle structure with very few melanin granules.
[0150] Test Example 7: Evaluation of Anti-oxidation and Anti-inflammation Effects of Composite Microneedle Patch in Vitiligo Model 1. Experimental Design and Sample Preparation Step 1: Strictly follow the animal model establishment method, grouping scheme and treatment process described in Test Example 6. Briefly, use vitiligo model mice, randomly group them, and then give them corresponding microneedle patches for three weeks. Collect skin tissue samples 24 hours after the last treatment for subsequent analysis.
[0151] 2. Oxidative Stress Level Evaluation Step 2.1: Skin tissue active oxygen detection. Prepare 8 μm frozen sections of mouse back skin tissue, fix with 4% paraformaldehyde, permeabilize with 0.1% Triton X-100, and block with 5% BSA. Then, incubate with ROS-specific primary antibody (1:200) at 4°C overnight, incubate with Cy3-labeled secondary antibody in the dark for 1 hour, and then re-stain with DAPI. Observe under a confocal microscope. Quantitative analysis shows that the ROS fluorescence intensity of the combined treatment group is significantly lower than that of the model group (p < 0.01), indicating that it effectively alleviates the oxidative stress state in the vitiligo model. Figure 28
[0152] Step 2.2: Anti-oxidation index detection. Prepare homogenate of skin tissue, and use commercial kits to measure SOD activity, CAT activity, and MDA content. The results show that the SOD / CAT activity of the vitiligo model group is significantly reduced, and the MDA level is increased. Each treatment group can reverse this trend, and the combined treatment group has the most significant effect on restoring antioxidant capacity. Figure 29
[0153] 3. Inflammatory Factor Expression Analysis Step 3.1: Immunohistochemical staining (). Figure 30 ). After dewaxing and hydration of the skin paraffin sections, antigen retrieval is performed. Then, incubate with rabbit anti-TNF-α monoclonal antibody (1:200) at 4°C overnight, incubate with HRP-labeled secondary antibody at room temperature for 1 hour, develop with DAB, re-stain with hematoxylin, and then quantitatively analyze the TNF-α positive expression area using ImageJ software.
[0154] Step 3.2: ELISA determination (). Figure 31 ). Take the skin tissue homogenate supernatant, follow the kit instructions, and quantitatively detect the concentrations of TNF-α and IL-6.
[0155] The results show that the G-Exos monotherapy group and the combined treatment group can significantly inhibit the expression of TNF-α and IL-6, and the combined treatment effect is better than that of the single treatment group.
[0156] The preferred embodiments of the application have been described above, but the application is not limited to the embodiments disclosed. Those skilled in the art can make modifications and changes to the embodiments disclosed herein without departing from the scope and spirit of the application.
Claims
1. A nanocomposite system for treating vitiligo, characterized in that, The invention comprises enzyme-responsive micelles and polyethylene glycol-modified polydopamine nanoparticles; the enzyme-responsive micelles are formed by encapsulating ginseng root exosomes with glyceryl monostearate; the polyethylene glycol-modified polydopamine nanoparticles are composed of a polydopamine core and a methoxy-polyethylene glycol-amine covalently linked; the enzyme-responsive micelles have an average hydrodynamic diameter of 150-250 nm and a zeta potential of -5 mV to -15 mV; the polyethylene glycol-modified polydopamine nanoparticles have an average hydrodynamic diameter of 150-170 nm and a zeta potential of -15 mV to -25 mV.
2. A smart microneedle patch for treating vitiligo, characterized in that, Its needle tip matrix is loaded with the nanocomposite system as described in claim 1.
3. The intelligent microneedle patch according to claim 2, characterized in that, The tips of the microneedle patch are made of photocrosslinked hydrogel, and the matrix material of the photocrosslinked hydrogel includes methacryloyl hyaluronic acid and polyvinyl alcohol.
4. The intelligent microneedle patch according to claim 2, characterized in that, The microneedles of the microneedle patch are conical, with a height of 700-800 μm and a base diameter of 450-550 μm.
5. A method for preparing a smart microneedle patch as described in any one of claims 2-4, characterized in that, Includes the following steps: (a) Methacrylamide hyaluronic acid, polyvinyl alcohol and photoinitiator are dissolved in water to form a base solution; (b) The nanocomposite system of claim 1 is mixed with the substrate solution to obtain a needle tip matrix solution; (c) The needle tip matrix solution is injected into the microneedle mold, centrifuged and filled, pre-dried, UV crosslinked and cured, covered with a backing layer, and demolded to obtain the product.
6. A pharmaceutical composition, characterized in that, The nanocomposite system comprising a therapeutically effective amount of the nanocomposite system as described in claim 1 and a pharmaceutically acceptable carrier.
7. The use of the nanocomposite system as described in claim 1 or the smart microneedle patch as described in any one of claims 2-4 in the preparation of a drug for the prevention and / or treatment of vitiligo.
8. The application of the nanocomposite system as described in claim 1 or the smart microneedle patch as described in any one of claims 2-4 in the preparation of medical devices for antioxidant and / or anti-inflammatory purposes.
Citation Information
Patent Citations
Bioactive material promoted stem cell secreted exosome in treatment of corneal injuries
CN108743620A
An immune-enhancing exosome hydrogel complex, its preparation method and application
CN112933113B
Polydopamine-exosome core / shell structure nanometer particles, intravascular stent material prepared after modification of polydopamine-exosome core / shell structure nanometer particles, and application of intravascular stent material
CN110237311A
Microneedle for treating vitiligo as well as preparation method and application thereof
CN114796097A
Double-layer drug-loaded microneedle for treating vitiligo as well as preparation method and application of double-layer drug-loaded microneedle
CN118078762A